Transcriptome Analysis Reveals the Molecular Mechanism of Potentilla anserina L. Polysaccharides in Mitigating Zearalenone-Induced Oxidative Stress in Porcine Sertoli Cells - Haixia Shi; Zunqiang Yan; Hong Du; Shuangbao Gun (Antioxidants)
Zearalenone (ZEA) is a widespread mycotoxin that contaminates cereals and other animal feeds. Sertoli cells (SCs) are the main target of attack by many environmental toxins. Our previous study found that Potentilla anserina L. polysaccharides (PAP-1b) exhibited protective effects against ZEA-induced oxidative damage in testicular SCs. However, the regulatory mechanisms remain incompletely characterized. In this study, SCs were treated with a complete medium (CON group) or medium containing 150 μg/mL PAP-1b (PAP-1b group). After 4 h, 100 μM ZEA was added to the ZEA group and PAP-1b-ZEA group, respectively. Samples were collected after the cells continued to be incubated for 48 h and subsequently subjected to transcriptome sequencing. The results showed that 1018, 7183, and 1023 differentially expressed genes (DEGs) were screened in the CON-vs.-PAP-1b, CON-vs.-ZEA, and ZEA-vs.-PAP-1b-ZEA groups, respectively. Among them, glutathione peroxidase 1 (GPX1) emerges as a key gene within this antioxidant defense mechanism. In addition, these DEGs were significantly enriched in Gene Ontology (GO) terms related to oxidative stress as well as in MAPK and PI3K-AKT signaling pathways, suggesting that PAP-1b effectively mitigated ZEA-induced oxidative damage in SCs by regulating these signaling pathways. These results provide an essential basis for the further elucidation of the role of PAP-1b in mitigating ZEA-induced oxidative damage in SCs.